Roosevelt's lost alliances : how personal politics helped start the Cold War - Costigliola, Frank, 1946- (Princeton University Press, 2012)
In the spring of 1945, as the Allied victory in Europe was approaching, the shape of the postwar world hinged on the personal politics and flawed personalities of Roosevelt, Churchill, and Stalin. Roosevelt's Lost Alliances captures this moment and shows how FDR crafted a winning coalition by overcoming the different habits, upbringings, sympathies, and past experiences of the three leaders. In particular, Roosevelt trained his famous charm on Stalin, lavishing respect on him, salving his insecurities, and rendering him more amenable to compromise on some matters. Yet, even as he pursued a las.